PRAKTIK SHADOW STATE DALAM PENYELENGGARAAN PEMERINTAHAN PADA PERIODE KEPEMIMPINAN SITI MASITHA-NURSOLEH DI KOTA TEGAL - Ismiati Nur Istiqomah; Yuwanto .; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
This research was conducted to discuss the phenomenon of shadow state that occurred in Tegal City during the period of SitiMasitha-Nursoleh leadership. To examine the figures indicated as actors behind the shadow state phenomena, the practice of shadow state phenomenon in Tegal City Government, and what impact the shadow state phenomenon have emerged. The research method used is a qualitative approach by collecting primary data through in-depth interviews with several informants from several parties. Required data for the study of documents related to the research. The results showed that the shadow state phenomenon in Tegal City Government during the period of leadership of Siti Masitha-Nusoleh indicated to occurr since the beginning of Siti Masitha-Nursoleh leadership. Shadow state phenomenon that happened in the form of the involvement of parties outside the formal government in managing government bureaucracy in the city of Tegal and the use of bureaucracy as a political tool for the interests of regional heads and actors outside the formal government.Keywords: Shadow State, Bureaucracy, Informal Government.